Determinants of halal policy implementation in Indonesia: an integrative value based approach - Sugeng Ribowo; Irfan Syauqi Beik; Immas Nurhayati; Nur Richana (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2026)
Purpose: This study analyzes the determinants of halal policy implementation in Indonesia within the framework of Islamic economic governance. The study focuses on how administrative, normative, and social factors influence the effectiveness of halal certification as part of national halal ecosystem development and MSME empowerment. Method: The research employs a qualitative evaluative design supported by Dynamic Regulatory Assessment (DRA). Data were collected through in-depth interviews, observation, and document analysis involving BPJPH, MUI, LPH, government institutions, and MSME actors. The analysis integrates George C. Edward III’s policy implementation theory, maqasid al-shariah, and Ibn Khaldun’s social solidarity concept. Findings: The results show that halal policy implementation is determined by six key factors: inter-institutional communication, human resource capacity, bureaucratic structure, implementer disposition, maqasid al-shariah values, and social solidarity among business communities. Communication between institutions is the most dominant factor affecting policy effectiveness. The study also finds that the halal regulatory system in Indonesia is still in a stabilization phase, characterized by uneven implementation, limited auditor capacity, procedural complexity for MSMEs, and varying levels of halal literacy across regions. Implication: This study contributes to Islamic economics and public policy literature by proposing a Value-Based Policy Implementation Model that integrates administrative rationality, spiritual values, and social dynamics. The model provides practical implications for strengthening halal governance through institutional coordination, human resource development, simplification of certification procedures, digital halal system integration, and community-based halal literacy programs.